DO MANAGER POLICIES LEAD TO CORPORATE IDIOSYNCRATIC RISK? - Jaren Jef Geovan Pinem; Amrie Firmansyah (Universitas Agung Podomoro, 2022)
Certain manager policies can push the company to be riskier. Some of the manager's policies include investment in investment opportunity sets, dividend policies and accrual policies through accrual earnings management. This study examines idiosyncratic risk with the three managers' policies. Tests were carried out using data from 75 food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2016 to 2020 using multiple linear regression analysis for panel data. The results suggest that investment opportunity set and accrual earnings management negatively affect idiosyncratic risk, whereas dividend policy positively affects idiosyncratic risk. This study places the investment opportunity set under test with idiosyncratic risk in the manager's policy framework, which is rarely used in previous studies.